Access audit on universal design: the case of Kota Kinabalu water front - Abdul Rahim, Asiah; Abdullah, Fadzidah (Common Ground, 2009)
Most developed countries have enforced the use of “Universal Design” in any physical development of their cities, for the purpose of eliminating discrimination among the society members towards the unfortunate handicapped persons. Nevertheless, in many developing countries, the awareness and inclusion of Universal Design is still in its initial stage. Cities’ authorities have not fully enforced the requirement of providing access to people with disability in their built environment; neither in public nor private spaces. The Department of Standard Malaysia (SIRIM) had initiated the publication of Malaysian Standards as guidelines for designers; architects, city planners, landscape architects, interior designers, and others who are involved in the construction of physical development with Universal Design. The Ministry also commissioned researchers to do access audit on various public spaces in several cities, to examine whether or not the cities’ public spaces are built in compliance of the Universal Design or not. This research describes the procedures, process and findings of the access audit done in the city of Kota Kinabalu. Simulation of the access audit utilised five (5) people, each with different type of disability such as: fully impaired vision, partially impaired vision, hearing impaired, wheel-chair bound, and a crutch user. With guidance from the researchers, the disabled respondents simulated their movements at the water front area of the city stretching about one (1) kilometre in length and 200 metres wide. The access audit done in Kota Kinabalu concluded that the water front area was designed without consideration of Universal Design, and renovation of the built environment is urgently needed to comply with the Malaysian standard requirements.